Efektivitas Kerjasama Pihak Ketiga Dalam Proses Pembinaan Warga Binaan Berbasis Masyarakat (Community Based Corrections) Lapas Terbuka Nusakambangan - Itmaamul Wafaa Samudra (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2021)
Collaborate with third parties between the Nusakambangan Open Prison and PT Noerman in the form of implementing the Community Based Correction concept in order to prepare social reintegration as mandated by PERMENKUMHAM No. 3 of 2018 concerning Conditions and Procedures for Granting Remission, Assimilation, Leave to Visit Family, Conditional Release, Leave Prior to Release, and Conditional Leave with reference to the 5 (five) principles put forward by P. Corney, namely the availability of employment opportunities, the existence of selection, not being exploited, minimum security, and responsibility for the transfer of Prisoner. This research was conducted to see the extent of the cooperation of third parties in implementing the concept of Community Based Correction in order to prepare towards social reintegration. The results of this study a comprehensive coaching and mentoring process because of the Terms of Reference (KAK) agreed upon by the Open Prison with PT Noerman which is stated in Number: PAS-19. HH 05.05 of 2019, Number: 01/PTNJA/PKS/IV/2019 of 2019 the Independence Development Program for correctional Prisoner in the field of Aquaculture Industry. This research was conducted using juridical-empirical research methods. This method is a research method that examines the applicable legal provisions and what happens in actual reality to find facts that are used as research data, which are then analyzed to identify problems and ultimately to solve problems. The approach used is a mixed approach between the rule of law and case studies.